THE PROCEDURAL ASPECTS OF ELECTRONIC EVIDENCE IN CIVIL LITIGATION: EXPERIENCE OF UZBEKISTAN - Pirmatov Otabek Shavkatovich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses the differences between electronic evidence and written, thing evidences, the problems of electronic evidence evaluation in civil litigation, electronic evidence, electronic documents, audio or video recordings, cellular messages (SMS, MMS), Internet and e-mail messages, disks and discs. Issues such as categorization, the admissibility of electronic evidence, and the improvement of electronic evidence in the current legislation.